Detecting hidden time patterns in football - Jonsson, G. K.; Borrie, A.; Bjarkadottir, S. H. (5th World Congress of Performance Analysis of Sport, 2001)
The game of football can be viewed as a coordinated and synchronized system of interrelated behaviour. A multivariate scale independent time pattern type, called T-patterns, has been defined for the detection of a particular kind of hidden patterning in streams of behaviour (Magnusson, 1983, 1988, 1996, 2000). Each of these patterns is characterized by significantly similar time intervals between its components over pattern occurrences. These patterns have a hierarchical structure, as each pattern component can be a simpler pattern of the same kind (see Figure 1). The pattern definition and the corresponding detection method focus on the relationships between the occurrence time's series of various behavioural event types. Such series also constitute the data for the pattern detection software, called THEME, which has been developed especially for the detection of such behaviour patterns. The THEME software was originally developed for the study of face-to-face human interactions, but its use has since been extended to other research areas. The software includes an optional module for the collection of data from digitized video recordings. Applications of this particular pattern detection approach in the analysis of human interaction are cited and illustrative examples of patterns detected in football presented.